Clinical, Serological, and Histopathological Similarities Between Severe COVID-19 and Acute Exacerbation of Connective Tissue Disease-Associated Interstitial Lung Disease (CTD-ILD) - Gagiannis, Daniel; Steinestel, Julie; Hackenbroch, Carsten; Schreiner, Benno; Hannemann, Michael; Bloch, Wilhelm; Umathum, Vincent G.; Gebauer, Niklas; Rother, Conn; Stahl, Marcel; Witte, Hanno M.; Steinestel, Konrad (Frontiers in Immunology, 2020)
Background and Objectives: Understanding the pathophysiology of respiratory failure in coronavirus disease 2019 (COVID-19) is indispensable for development of therapeutic strategies. Since we observed similarities between COVID-19 and lung manifestations of connective tissue disease (CTD-ILD), we investigated features of autoimmunity in SARS-CoV-2-associated respiratory-failure. Methods: We prospectively enrolled 22 patients with RT-PCR-confirmed SARS-CoV-2 infection and 10 patients with non-COVID-19-associated pneumonia. Full laboratory testing was performed including autoantibody (AAB; ANA/ENA) screening using indirect immunofluorescence (IIF) and immunoblot (IB). Fifteen COVID-19 patients underwent high-resolution computed tomography (HR-CT). Transbronchial biopsies/autopsy tissue samples for histopathology and ultrastructural analyses were obtained from 4/3 cases, respectively. Results: Thirteen (59.1%) patients developed acute respiratory distress syndrome (ARDS), and five patients (22.7%) died from disease. ANA titers ≥1:320 and/or positive ENA immunoblot were detected in 11/13 (84.6%) COVID-19 patients with ARDS, in 1/9 (11.1%) COVID-19 patients without ARDS (p=0.002) and in 4/10 (40%) patients with non-COVID-19-associated pneumonias (p=0.039). Detection of AABs was significantly associated with a need for intensive care (ICU) treatment (83.3% vs. 10%; p=0.002) and occurrence of severe complications (75% vs. 20%, p=0.03). Radiological and histopathological findings were highly heterogeneous including patterns reminiscent of exacerbating CTD-ILD, while ultrastructural analyses revealed interstitial thickening, fibroblast activation and deposition of collagen fibrils. Conclusions: We are the first to report overlapping clinical, serological and imaging features between severe COVID-19 and acute exacerbation of CTD-ILD. Our findings indicate that autoimmune mechanisms determine both clinical course and long-term sequelae after SARS-CoV-2 infection, and the presence of autoantibodies might predict adverse clinical course in COVID-19 patients.